PENGARUH PERHATIAN ORANGTUA DAN PERGAULAN BEBAS TERHADAP PERKEMBANGAN MORAL ANAK PADA SISWA SMP - Harvi Nurinsani Khoirul Anam; Neng Siti Sopiah; Latifah Latifah (IKIP Siliwangi, 2019)
The matter of this research is based on human development and a variety of new habits that require the adjustment of individuals who are more mentally stable. The existence of the development of the times which raises new norms or rules requires humans to be able to adjust to the conditions that occur. The many positive and negative impacts that result from these developments make people have to be able to choose and sort out something good or bad. From these problems, the researcher limits the discussion of this study to the problem of influence and the role of parents on children's moral development. This study aims to analyze various influences and effects of the environment, free association, and technology on children's moral changes in character formation. The method used in this study uses descriptive methods that allow researchers to obtain data and describe without giving special treatment or in accordance with the facts found by researchers. The results of the analysis of this study indicate that children's moral development is influenced by various factors including environmental factors, technology, and promiscuity, to avoid the impact of these factors the role of parents is very much needed in providing guidance and advice.